Soil properties, rhizosphere bacterial community, and plant performance respond differently to fumigation and bioagent treatment in continuous cropping fields - Xiong, Jing; Peng, Shuguang; Liu, Yongjun; Yin, Huaqun; Zhou, Lei; Zhou, Zhicheng; Tan, Ge; Gu, Yabing; Zhang, Hetian; Huang, Jingyi; Meng, Delong (Frontiers in Microbiology, 2022)
Abstract Continuous cropping barriers lead to huge agriculture production losses, and fumigation and biological agents are developed to alleviate the barriers. However, there is a lack of literature on the differences between strong chemical fumigant treatment and moderate biological agent treatment. In this study, we investigated those differences and attempted to establish the links between soil properties, rhizosphere microbial community, and plant performance in both fumigation and bioagent treated fields. The results showed that the fumigation had a stronger effect on both soil functional microbes, i.e. ammonia oxidizers and soil-borne bacterial pathogens, and therefore led to a significant change in soil properties, higher fertilizer efficiency, lower disease infections, and improved plant growth, compared to untreated control fields. Biological treatment caused little changes to soil properties, rhizosphere bacterial community, and plant physiology. Correlation and modeling analyses revealed that the bioagent effect was mainly direct, whereas fumigation resulted in indirect effects on alleviating cropping barriers. A possible explanation would be the reconstruction of the soil microbial community by the fumigation process, which would subsequently lead to changes in soil characteristics and plant performance, resulting in the effective alleviation of continuous cropping barriers.